Draft Tenth Five Year Plan 2002-07 and Annual Plan 2002-03(Scheme-Wise Details) - Planning Commission (Planning Commission, 2002)
The territory of Pondicherry merged with the Indian Union with effect from 01.11.1954 in accordance with the de-facto agreement between the Government of India and the government of France, which was signed on 21.10.1954. De-jure transfer of Pondicherry took place on 16th August, 1962. Thereafter the Union Territory of Pondicherry consisting of the regions of Pondicherry, Karaikal, Mahe and Yanam has been administered under the provisions of Government of Union Territories Act, 1963.
Union Territory of Pondicherry